Produção e qualidade de sementes de guandu: efeitos de doses de fósforo, potássio e espaçamentos em duas épocas de semeadura - Bertolin, Danila Comelis [UNESP]; de Sa, Marco Eustaquio [UNESP]; Buzetti, Salatier [UNESP]; Santiago, Denis [UNESP]; Barbosa, Rafael Marani [UNESP] (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2008)
The present work had as objective to evaluate the effect of five phosphorus doses and four potassium doses in two inter-row plant spacings at two sowing times in the production and quality of pigeon pea seeds, in Selviria, State of Mato Grosso do Sul, Brazil. For the determination of treatment effect, a completely randomized block design was used, in a 2x2x5x4 factorial, with four replications. The treatments were 0, 40, 80, 120 and 160 kg ha(-1) of P(2)O(5); 0, 30, 60 and 90 kg ha(-1) of K(2)O; inter-row plant spacings were 0.50 and 0.30 m; and sowing times were December 2003 and February 2004. The first sowing generated greater productivity, whereas the second sowing produced better seed quality. The 0.50 m spacing generated heavier seeds, while the 0.30 m spacing made for seeds of greater quality. Phosphorus, in general, influences positively in the production and quality of the seeds.
Production and quality of pigeon pea seeds: effect of phosphorus and potassium levels, and spacing at two sowing times
Keywords: Cajanus cajan; density; fertilization